Modifying the Thioester Linkage Affects the Structure of the Acyl Carrier Protein. Issue 32 (2nd July 2019) - Sztain, Terra; Patel, Ashay; Lee, D. John; Davis, Tony D.; McCammon, J. Andrew; Burkart, Michael D.
Abstract: At the center of many complex biosynthetic pathways, the acyl carrier protein (ACP) shuttles substrates to appropriate enzymatic partners to produce fatty acids and polyketides. Carrier proteins covalently tether their cargo via a thioester linkage to a phosphopantetheine cofactor. Due to the labile nature of this linkage, chemoenzymatic methods have been developed that involve replacement of the thioester with a more stable amide or ester bond. We explored the importance of the thioester bond to the structure of the carrier protein by using solution NMR spectroscopy and molecular dynamics simulations. Remarkably, the replacement of sulfur with other heteroatoms results in significant structural changes, thus suggesting more rigorous selections of isosteric substitutes is needed. Abstract : One Atom Matters : The effect of replacing the thioester S atom of acyl carrier protein (ACP) with N or O to give more stable amide or ester bonds was investigated through NMR spectroscopy and MD simulations. Although ACP contains over 1000 other atoms, this single‐atom replacement results in significant structural perturbations. Rigorous evaluation is thus needed to inform the proper selection of isosteric substitutes for developing chemical biology tools.